Influência das Condições de Encapsulamento em Alginato e da Suplementação com Nutrientes sobre a Fermentação de Xilose por Saccharomyces cerevisiae recombinante - Rosa, Daniella Guimarães (Universidade Federal de São Carlos, 2020)
The implementation of the second-generation (2G) bioethanol’s industrial production using recombinant yeast relies on developing proper fermentation strategies to obtain ethanol in high concentrations from hemicellulosic concentrated hydrolysates, containing inhibitory compounds. Several studies relate the protection effect given by alginate gel, whilst other mention that supplementation with lipids and nutrients rich in protein can contribute to a higher ethanol tolerance. Therefore, the main objective of this work is to evaluate the influence of alginate gel microcapsules, enriched (or not) with key nutrients, on the performance of xylose fermentation by immobilized recombinant yeast, through Plackett-Burman’s experimental design with experiments carried out under medium A (without ethanol supplementation) and medium B (with ethanol supplementation). In the first place, a specific study was conducted to assess the chosen levels for the fermentative medium’s supplementation. For this purpose, experiments using enriched medium with different concentrations of peptone, yeast extract, glycerol and oleic acid were performed. Similarly, experiments to evaluate ethanol’s initial concentration to be used in the experimental design runs under ethanol supplementation (medium B) were also conducted. All experiments were carried out inside mini reactors with 8 mL of useful volume, containing 3 mL of medium YPX (yeast extract, peptone, and xylose) and 3 mL of rS. cerevisiae MDS130 immobilized in calcium alginate, under 35 oC and stationary condition. The fermentations were monitored by mass loss associated to CO2 release and, at the end of each batch, the supernatant was stored to posterior analysis of its sugar and metabolites concentrations through high performance liquid chromatography. Cells viability after the batches were determined in Neubauer chamber, after capsules disruption and staining with methylene blue. Then, the Plackett-Burman’s design runs using a PB12 matrix was carried out. The selected studied factors were: sodium alginate mass fraction, capsule diameter, peptone concentration, yeast extract concentration, glycerol mass fraction, and oleic acid mass fraction. For the statistical analysis, the responses volumetric productivity (Qp [g/L.h]), ethanol selectivity (S [get/gxil]), overall ethanol yield (Yp/s [get/gxil]), and final conversion (Xf [%]) were chosen. Thus, according to the statistical analysis results, the capsule’s diameter and the concentrations of glycerol and yeast extract were identified as the factors that presented significant effects over the performance of recombinant Saccharomyces cerevisiae xylose’s fermentation.
Influence of alginate entrapment conditions and nutrient supplementation on xylose fermentation by recombinant Saccharomyces cerevisiase
Keywords: etanol 2G, Saccharomyces cerevisiae, fração hemicelulósica; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA